KELIMPAHAN DAN KERAGAMAN JENIS SERANGGA HAMA JAGUNG DI BERBAGAI GUDANG PENYIMPANAN - Srinita Arifin; Sylvia Sjam; Ayu Kartini Parawansa (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2022)
Corn (Zea mays L.) is a strategic commodity in Indonesia after rice because corn is not only used as food but also as animal feed. This corn commodity is generally stored in the form of shelled seeds. One of the obstacles in the storage process is the presence of warehouse pests. Warehouse pests are plant-destroying organisms that work when plants are stored in storage rooms or warehouses. This study aims to determine the diversity, abundance and dominance of corn pests in sacks and scattered and determine the weight loss and damage to corn kernels in several warehouses. Determination of the number of samples used in this study was by using descriptive survey methods and qualitative data in several warehouses, then the samples were reared for 30-35 days (± a month). Sampling was carried out 8 times with an interval of 2 times a week. The results of the research showed that the diversity of pests was obtained, namely Tribolium castaneum Herbst (Coleoptera: Tenebrionidae), Rhizopert dominica Fabricius (Coleoptera: Bostrichidae), Sitophilus sp Linnaeus (Coleoptera: Curculionidae), Alphitobius diaperinus Panzer (Coleoptera: Tenebrionidae), Carpteraphilus di (Coleoptera: Midia : Nitidulidae), Cryptolestes ferrugineus Stephens (Coleoptera: Cucujidae), Corcyra cephalonica Stantion (Lepidoptera: Pyralidae), Lasioderma serricorne Fabricius (Coleoptera: Anobiidae), Palorus depressus Fabricius (Coleoptera: Tenebrionidae). The highest abundance and dominance was in the pests Sitophilus sp. Linnaeus (Coleoptera: Curculionidae) and Tribolium castaneum Herbst (Coleoptera: Tenebrionidae). The highest percentage of weight loss and damage to corn kernels was found in warehouse A, while the lowest weight loss and damage to corn kernels was in warehouse C.